Predicted mbira found - Tracey, Andrew (International Library of African Music, 2013)
This article is written as a follow-up to my article "The original African mbira?” (1972). I can report that an instrument which I predicted to have existed in that article actually did/does exist! In the original article I compared the tuning layouts of two related present-day members of the mbira family, hera, also called matepe, (found in northern Zimbabwe and northeast Zimbabwe into Mozambique) and nyonganyonga (found in central Mozambique, from Mutare, Zimbabwe to Beira, Mozambique and also into southern Malawi).
Keywords: African Music